The Cell Cycle Checkpoint Regulator ATR Is Required for Internal Aluminum Toxicity-Mediated Root Growth Inhibition in Arabidopsis - Zhang, Yang; Guo, Jinliang; Chen, Mo; Li, Lun; Wang, Lihua; Huang, Chao-Feng (Frontiers in Plant Science, 2018)
Aluminum (Al) can target multiple sites of root cells for toxicity, including the cell wall, the plasma membrane and symplastic components. Previous work revealed that the cell cycle checkpoint regulator (ATR) Ataxia Telangiectasia-mutated and Rad3-related is required for Al toxicity-induced root growth inhibition in als3 and that the symplastic component DNA is an important target site of Al for the toxicity. However, whether monitoring DNA integrity through ATR-regulated pathway is required for Al-induced root growth inhibition in other Al-sensitive mutants remains unknown. In this study, we demonstrated that the atr mutation could also rescue the Al hypersensitivity and Al-induced cell cycle arrest in star1, which supports the hypothesis that ALS3 and STAR1 function together to be involved in the detoxification of Al in Arabidopsis. However, mutation of ATR could not rescue the Al-sensitive phenotype of almt1 or stop1, both of which are defective in external detoxification mechanisms of Al. We further showed that the Al hypersensitivity and Al-induced quiescent center (QC) differentiation in als1 could also be rescued by the atr mutation. Therefore, our results suggest that ATR-regulated pathway is involved in the modulation of internal Al toxicity-mediated root growth inhibition in Arabidopsis.